IMPLEMENTASI KEBIJAKAN SISTEM ZONASI (PERMENDIKBUD) TENTANG PENERIMAAN PESERTA DIDIK BARU TAHUN AJARAN 2024/2025 DI SEKOLAH DASAR NEGERI 12 PEMECUTAN KAJA (Sindoro: Cendikia Pendidikan, 2025)
This study aims to determine the implementation of the zoning system policy based on the Minister of Education Regulation (PERMENDIKBUD) concerning the New Student Admission (PPDB) for the 2024/2025 academic year at SDN 12 Pemecutan Kaja. The method used is a qualitative approach with observation, interviews, and documentation study. The results showed that the implementation of the zoning policy still faces obstacles, such as the lack of public understanding of the zoning system, insufficient socialization from the education office, and technical issues in data entry. Therefore, improvements in communication, resources, and bureaucratic support are needed to ensure equitable education implementation.